IDENTIFIKASI POTENSI PENGEMBANGAN DAN TAMPILAN FISIK KIMIA RUMPUT LAUT DI BEBERAPA WILAYAH PERAIRAN NTT - Maria Susana Medho; Endeyani V. Muhamad (Politeknik Pertanian Negeri Kupang, 2017)
The aim of the research is to identify sea weed potential development, sea weed for carragenan, and sea weed post harvest handling in several coastal area in East Nusa Tenggara that is Alor, Sumba, Sabu, and Kupang. The research have done in two stage. The first stage is identify potential developmen and the kind of seaweed, time of harvest, and post harvest handling. The second stage is extraction to indentify functional structure seaweed that is classified in kappa carragenan or iota carragenan. Result of the research show that seaweed that is cultivated at Alor and Tablolong Kupang coastal classified Estriatum Sakul. This seaweed have clump with short branch, relatively small thallus diameter and cylindris, green colour and slick surface.The harvesting time of this seaweed aproximately 45 - 60 days. Seaweed from coastal Sabu and Sumba classified as Eucheuma cottonii with relatively long branch and cylindris talus. Seaweed from Sabu have red green colour and from Sumba have green yellow. The harvesting time of seaweed from Sabu and Sumba approximately 30 - 60 days. The other seaweed from Tablolong Kupang classified Eucheuma cottonii with different colour that is red . This seaweed have big and long talus. All of the seaweed from this several coastal area have carragenan functional structure is kappa or iota carrageenan. the most high rendemen carragenan is Estriatum Sakul from Alor with 47,5 %, followed by Eucheuma cottonii 41,5 %from Tablolong Kupang and Estriatum Sakul 35,41 % Key Words: Identification, Seaweed, Carragenan